Sodium transport system in plant cells - Yamaguchi, Toshio; Hamamoto, Shin; Uozumi, Nobuyuki (Frontiers in Plant Science, 2013)
Since Sodium, Na, is a non-essential element for the plant growth, the molecular mechanism of Na+ transport system in plants has remained elusive for the last two decades. The accumulation of Na+ in soil through irrigation for sustainable agricultural crop production, particularly in arid land, and by changes in environmental and climate conditions leads to the buildup of toxic level of salts in the soil. Since the latter half of the 20th century, extensive molecular research has identified several classes of Na+ transporters that play major roles in the alleviation of ionic stress by excluding toxic Na+ from the cytosol or preventing Na+ transport to the photosynthetic organs, and also in osmotic stress by modulating intra/extracellular osmotic balance. In this review, we summarize the current knowledge of three major Na+ transporters, namely NHX, SOS1 and HKT transporters, including recently revealed characteristics of these transporters.